Missed diagnoses: Clinically relevant lessons learned through medical mysteries solved by the Undiagnosed Diseases Network. Issue 10 (30th July 2020) - Cope, Heidi; Spillmann, Rebecca; Rosenfeld, Jill A.; Brokamp, Elly; Signer, Rebecca; Schoch, Kelly; Kelley, Emily G.; Sullivan, Jennifer A.; Macnamara, Ellen; Lincoln, Sharyn; Golden‐Grant, Katie; ,; et al.
Abstract: Background: Resources within the Undiagnosed Diseases Network (UDN), such as genome sequencing (GS) and model organisms aid in diagnosis and identification of new disease genes, but are currently difficult to access by clinical providers. While these resources do contribute to diagnoses in many cases, they are not always necessary to reach diagnostic resolution. The UDN experience has been that participants can also receive diagnoses through the thoughtful and customized application of approaches and resources that are readily available in clinical settings. Methods: The UDN Genetic Counseling and Testing Working Group collected case vignettes that illustrated how clinically available methods resulted in diagnoses. The case vignettes were classified into three themes; phenotypic considerations, selection of genetic testing, and evaluating exome/GS variants and data. Results: We present 12 participants that illustrate how clinical practices such as phenotype‐driven genomic investigations, consideration of variable expressivity, selecting the relevant tissue of interest for testing, utilizing updated testing platforms, and recognition of alternate transcript nomenclature resulted in diagnoses. Conclusion: These examples demonstrate that when a diagnosis is elusive, an iterative patient‐specific approach utilizing assessment options available to clinical providers may solve a portion of cases. However, this does require increased provider time commitment, a particular challenge in the current practice of genomics.